2010
DOI: 10.1371/journal.pone.0015330
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Disruption Accelerates Tumor Growth and Angio/Stromagenesis through a Wnt Signaling Pathway

Abstract: Epidemiologic studies show a high incidence of cancer in shift workers, suggesting a possible relationship between circadian rhythms and tumorigenesis. However, the precise molecular mechanism played by circadian rhythms in tumor progression is not known. To identify the possible mechanisms underlying tumor progression related to circadian rhythms, we set up nude mouse xenograft models. HeLa cells were injected in nude mice and nude mice were moved to two different cases, one case is exposed to a 24-hour light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 39 publications
6
50
0
1
Order By: Relevance
“…These studies demonstrate that disruption of circadian endocrine rhythms either by constant light exposure or pinealectomy increases spontaneous and carcinogen-induced mammary gland and hepatocellular carcinogenesis in rodents 114–116 . Similar experiments conducted in recent years have also shown that disruption of circadian homeostasis by a short period of back-and-forth or consecutive phase advance shifts of environmental light cues, or by constant light exposure significantly accelerate tumor growth in animals 117121 . Compared to sham-operated animals, mice lacking a central clock due to surgical ablation of the SCN were unable to maintain circadian rhythmicity in locomotor activity, body temperature and immune function.…”
Section: Circadian Disruption Promotes Cancer Development In Animal Msupporting
confidence: 65%
“…These studies demonstrate that disruption of circadian endocrine rhythms either by constant light exposure or pinealectomy increases spontaneous and carcinogen-induced mammary gland and hepatocellular carcinogenesis in rodents 114–116 . Similar experiments conducted in recent years have also shown that disruption of circadian homeostasis by a short period of back-and-forth or consecutive phase advance shifts of environmental light cues, or by constant light exposure significantly accelerate tumor growth in animals 117121 . Compared to sham-operated animals, mice lacking a central clock due to surgical ablation of the SCN were unable to maintain circadian rhythmicity in locomotor activity, body temperature and immune function.…”
Section: Circadian Disruption Promotes Cancer Development In Animal Msupporting
confidence: 65%
“…Stress induces hypothalamic signaling which activates the sympathetic nervous system, ultimately resulting in the systemic release of norepinephrine/epinephrine. Stress may also be an important factor that influences activation of dormant DTCs after long periods of time in marrow through immune system suppression (11), activating release of pro-inflammatory mediators (12,13), and activation of neurotransmitters from adrenergic neurons (14,15). Growing evidence supports the observation that β-adrenergic receptor antagonists, which interfere with norepinephrine ( NE ) signaling, may reduce cancer relapse or slow disease progression (1619).…”
Section: Introductionmentioning
confidence: 99%
“…The disturbances occur in both sleep initiation and sleep maintenance. Epidemiologic studies show high incidence of cancer in shift workers [36]. The finding suggests that circadian disruption induces the progression of malignant tumors via a Wnt signaling pathway.…”
Section: Cancermentioning
confidence: 95%